Manfaat Prenatal Yoga untuk Mengatasi Ketidaknyamanan pada Ibu Hamil di Desa Pamulihan - Dewi Sagitaria, Bian; Yulia Nur Khayati; Ekawati, Rahmi; Murtiningsih, Sri; Rahmawati, Yenny; Trianingsih (Universitas Ngudi Waluyo, 2024)
Pregnancy is a time full of hope and challenges for every mother, which is often caused by physical complaints such as back pain, difficulty sleeping, and anxiety. Prenatal yoga is here as a safe and effective solution to help pregnant women overcome these discomforts. This community service activity aims to increase the knowledge and skills of pregnant women in Pamulihan Village, Larangan District, Brebes Regency, regarding the benefits of prenatal yoga through educational sessions and practicing yoga movements. The activity involved 15 participants from various trimesters of pregnancy who were selected based on certain criteria. Education is delivered in the form of presentations, distribution of leaflets, and direct practice of yoga movements designed to suit the physical needs of pregnant women. Evaluation was carried out through pre-test and post-test, which showed a significant increase in participants' knowledge, from 20% in the